1960
DOI: 10.1152/ajplegacy.1960.198.1.4
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of effects of thyroidectomy with propylthiouracil treatment on renal hypertension in rats

Abstract: Surgical thyroparathyroidectomy (thyroidectomy) prevented the rise in systolic blood pressure to hypertensive levels in rats whose kidneys were bilaterally encapsulated with latex envelopes. This treatment also reduced the systolic blood pressure of ‘normal,’ nonencapsulated rats. The antithyroid drug, propylthiouracil (PTU), acted in the same fashion as surgical thyroidectomy on blood pressure of both kidney encapsulated and nonencapsulated rats. However, PTU appeared to be a more effective treatment than thy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1961
1961
1990
1990

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Fregly 22 reported that SHR had lower l3l I-uptake by the thyroid gland than normotensive control animals. However, thyroidectomy or administration of propylthiouracil prevented the expected rise in BP, both in renal hypertension 23 and in NaCl-induced hypertension in rats. 24 Serum T 4 concentrations are lower in the prehypertensive stage of SHR, but thyroidectomy at this stage prevents the later development of hypertension.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Fregly 22 reported that SHR had lower l3l I-uptake by the thyroid gland than normotensive control animals. However, thyroidectomy or administration of propylthiouracil prevented the expected rise in BP, both in renal hypertension 23 and in NaCl-induced hypertension in rats. 24 Serum T 4 concentrations are lower in the prehypertensive stage of SHR, but thyroidectomy at this stage prevents the later development of hypertension.…”
Section: Resultsmentioning
confidence: 93%
“…24 Serum T 4 concentrations are lower in the prehypertensive stage of SHR, but thyroidectomy at this stage prevents the later development of hypertension. 23 These observations in SHR were made in relation to the systolic BP. If they have any bearing on the pathogenesis of hypertension in humans, they may be more related to isolated systolic hypertension, such as that seen in 20% of our thyrotoxic patients, than to diastolic hypertension.…”
Section: Resultsmentioning
confidence: 99%